Efeitos inflamatórios e imunitários da Colectomia esquerda por Laparoscopia e por Laparotomia em suínos - Juliano Alves Figueiredo (2011)
The use of animal models in laparoscopy of the large bowel is useful to study inflammatory and immunity per and postoperative aspects. Acute phase reaction and phagocytosis in both techniques, were not compared. The purpose of this investigation was to assess the inflammatory postoperative response to laparoscopic colectomy comparative with open surgery. The groups consisted as follows: Group A(n = 5) – no surgical intervention, Group B(n = 5) – laparotomy left colectomy, Group C(n = 5) – only laparotomy, Group D(n = 8) – laparoscopic left colectomy, Group E (n = 5) – only laparoscopy. These groups were studied on the following parameters: acid base disorders after laparoscopic colectomy and spontaneous ventilation, acute phase proteins, albumin and fibrinogen, interleukin 6 values and incidence of the reticuloendothelial phagocytic system. The main variables studied were blood pH levels, total luekocytes count, monocyte percentages, liver, spleen and lungs phagocyte macrophages carbon particle, albumin and fibrinogen, interleukin 6. These parameters were analyzed before of the surgery, two hours after this surgery and three days after surgery. The results showed that laparoscopic colectomy with spontaneous ventilation combined with carbon dioxide pneumoperitoneum did not affect acid base homeostasis. On the thrid day postoperative left colectomy by laparotomy resulted in less percentages of peripheral blood monocytes and higher fibrogen as well as higher rates of total leukocytes and total iron-binding capacity. Liver, spleen and lungs phagocytosis percentages were not different in all of the groups submitted to surgery. The interleukin 6 values was not different in groups that underwent surgical laparoscopy and laparotomy. Our results colectomy through laparoscopy is more advantageous, inflammatory and immunity advantages, them by mean of laparotomy.